On the Local Well-posedness for the Dumbbell Model of Polymetic Fluids (Journal of Partial Differential Equations, 2008)
In this paper, we consider the local well-posedness of smooth solutions to a coupled microscopic-macroscopic model for polymeric fluid in general space dimension and with general initial data in Hölder space.